Kierunki gospodarowania w regionach przyrodniczo cennych w aspekcie integracji z Unią Europejską (na przykładzie Podkarpacia) - Kaliszczak, Lidia; Smoleń, Marek (Directions of Managing in Regions of Natural Value within the Context of the Integration with the European Union (on the Example of Podkarpacie), 2005)
In the paper the anticipated directions of economy administration in Podkarpacie province is introduced. The changes which occured after joining the European Union are taken under consideration. The solutions which create the chance for the increase of competitiveness exploiting the local resources are pointed. The researched area is predestined to the agricultural, tourist-recreational, health resort and industrial functions, which are in complementary relations towards one another.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 384-389